Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-34134-x_17
|View full text |Cite
|
Sign up to set email alerts
|

A Minimum CR2 Binding Domain of C3d Enhances Immunity Following Vaccination

Abstract: The degradation product of the third (C3) complement component, C3d, links innate and adaptive immunity, and the covalent attachment of C3d to an antigen enhances antigen-specific immune responses. C3d has been hypothesized to enhance immunity by direct interaction with complement receptor 2 (CR2/CD21) on immune cells. However, the domains on C3d important for CR2 binding have been controversial, with various studies reaching contradictory conclusions. In addition, the concept of B-cell activation via CR2 by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 62 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…CD21 is also known as CR2 and is the C3d receptor; interaction of this receptor with C3d activates B-cells [1417]. CR2 is expressed on B cells, follicular dendritic cells, epithelial cells, and a sub-group of T cells [16]. Interaction of CD21 with C3d activates B-cells creates immunologic memory, and causes immunoglobulin class switching but conversely is involved in B cell tolerance [17].…”
Section: Introductionmentioning
confidence: 99%
“…CD21 is also known as CR2 and is the C3d receptor; interaction of this receptor with C3d activates B-cells [1417]. CR2 is expressed on B cells, follicular dendritic cells, epithelial cells, and a sub-group of T cells [16]. Interaction of CD21 with C3d activates B-cells creates immunologic memory, and causes immunoglobulin class switching but conversely is involved in B cell tolerance [17].…”
Section: Introductionmentioning
confidence: 99%
“…The co‐activation of these two signals has been shown to lower the threshold of activation and to promote a more robust immune response by inducing isotype switching, somatic hypermutation and B‐cell memory generation 4 . Yet in mice lacking complement receptors CR1 (CD35) and CR2 (CD21), immune responses to protein antigen‐C3d conjugates were equally enhanced to the levels seen in wild‐type mice 5 , 6 , 7 . Further, C3 −/− mice, but not CD21 −/− , have been shown to be deficient in T‐dependent (Td) responses 8 .…”
mentioning
confidence: 99%
“…It was previously reported that fusion of multimers of the P28 peptide to an antigen may enhance the level of immunogenicity (Bergmann-Leitner et al, 2007;Bower & Ross, 2006). Thus, hemagglutinin sequence (GenBank ABQ45850) from the influenza A virus (A/chicken/India/NIV33487/2006, H5N1, clade 2.2) was fused to 4 copies of P28 sequence to make H5-P28 4 (Figures 1a-I).…”
Section: Methodsmentioning
confidence: 95%